STRATEGY FOR DEVELOPING CASSAVA LEAF ANIMAL FEED ( MANIHOT UTILISSIMA ) (CASE STUDY: SUMBEREJO VILLAGE, PAGAR MERBAU DISTRICT, DELI SERDANG REGENCY) - Henny Pratiwi; Rasidah Sihombing (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the development strategy of cassava leaf-based animal feed ( Manihot utilissima ) in Sumberejo Village, Pagar Merbau District, Deli Serdang Regency. This study uses a nonprobability sampling method with a saturated sampling technique. With a total of 53 respondents consisting of 50 consumers, 1 business owner and 2 employees. This study uses primary and secondary data. This study uses multiple linear regression analysis to determine what factors influence the development strategy of cassava leaf animal feed and descriptive analysis to analyze the development strategy for the potential and opportunities of using cassava leaves as animal feed. This research method uses qualitative and quantitative analysis. The results showed that cassava leaves have a high crude protein content, which is around 20-30%, and contain crude fiber, fat, and minerals that are beneficial for livestock growth. Multiple linear regression analysis in this study shows that all independent variables have a significant effect on the dependent variable. Among these factors, the economic aspect makes the largest contribution, making it the main factor influencing the dependent variable. Furthermore, social aspects and external support also play a significant role in determining the results. In addition, other factors such as technology, resources, and marketing and distribution also have a significant impact, although with a smaller influence compared to economic and social aspects. Thus, the regression model shows a positive relationship between the independent variables and the dependent variable, so that improvements in these aspects will increase the dependent variable, with the main priority on economic and social aspects.